2018
DOI: 10.1097/mlr.0000000000000832
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Consequences of Axillary Lymph Node Dissection in the Era of Sentinel Lymph Node Biopsy for Breast Cancer

Abstract: In this pathologically node-negative population-based breast cancer cohort, only half underwent solely SLNB. Patients treated by low-volume surgeons were more likely to undergo ALND. Resources and guidelines on the appropriate training and competency of surgeons to assure the optimal performance of SLNB should be considered to decrease rates of potentially avoidable ALND and lymphedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Initiatives such as Choosing Wisely Canada have attempted to increase awareness about this topic in recent years [35]. In our study, we found that 5.8% of women in Manitoba with node-negative cancer underwent an ALND, but that the number varied greatly by surgery geographic locations; other studies from other jurisdictions found this number to be as high as 49% [36]. Therefore, Manitoba meets the minimum standard published by EUSOMA as well as the target, but on a global scale, but some centers are falling well behind this benchmark.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Initiatives such as Choosing Wisely Canada have attempted to increase awareness about this topic in recent years [35]. In our study, we found that 5.8% of women in Manitoba with node-negative cancer underwent an ALND, but that the number varied greatly by surgery geographic locations; other studies from other jurisdictions found this number to be as high as 49% [36]. Therefore, Manitoba meets the minimum standard published by EUSOMA as well as the target, but on a global scale, but some centers are falling well behind this benchmark.…”
Section: Discussionmentioning
confidence: 56%
“…Breast-conserving surgery was the most common procedure (66.7%) followed by mastectomy without immediate reconstruction (22.8%) and mastectomy with immediate reconstruction (10.5%). The youngest age group (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) underwent the highest percentage of mastectomy with immediate reconstruction (36.1%; 95% CI: 27.9 to 44.3). This percentage decreased with increasing age.…”
Section: Surgical Treatment Patternsmentioning
confidence: 99%
“…Sentinel lymph node biopsy (SLNB) serves as an optimal choice for those without clinical or radiological evidence of ALN metastasis. It has been considered to be an ideal procedure for patients whose sentinel lymph node (SLN) are negative (4, 5) or those with 1–2 positive SLN (6, 7). However, second procedure of ALND or radiotherapy is unavoidable to adequately deal with axilla if SLN metastasis was found (8).…”
Section: Introductionmentioning
confidence: 99%
“…MDCT can obtain high-quality multiplanar images in fast scan time and allow three-dimensional reconstruction (17). Furthermore, preoperative MDCT can be performed with the patient in the supine position, which facilitates simultaneous localization of the lesion, and evaluation of its extent, as well as examination of the skin, chest wall, and regional lymph nodes, including both axillae, internal mammary, and supraclavicular chains (5, 8, 18). However, preoperative MDCT for evaluating ALN status in patients with breast cancer remains under-investigated (18, 19).…”
Section: Introductionmentioning
confidence: 99%
“…Accurate assessment of ALN disease burden is vital in staging breast cancer, which guides multidisciplinary treatment decision making nowadays [ 2 , 3 ]. Sentinel lymph node (SLN) biopsy (SLNB) is now widely used as the gold standard for axillary staging in clinically node-negative breast cancer in National Comprehensive Cancer Network (NCCN) guidelines [ 4 ], which reduces the complications of lymphedema and other arm morbidity to a certain extent compared with axillary lymph node dissection (ALND) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%